Persistent visual impairments following mild-to-moderate ischemic stroke - Wijesundera, Chamini Niroshika; Crewther, Sheila Gillard; Wijeratne, Tissa; Vingrys, Algis J. (Frontiers in Ophthalmology, 2025)
BackgroundVision is rarely appraised either acutely or during recovery, following acute ischemic stroke. Our previous study found significant deficits in visual function after 2 to 3 days in ~68% of hospitalized mild-to-moderate acute ischemic stroke (AIS) patients with no comorbid eye disease. The purpose of this study was to evaluate recovery in vision after 2–6 months in a subgroup of the original participants.MethodsVisual assessments were performed within the first week of admission and 2–6 months later. Testing was achieved on an iPad and included visual acuity (VA), VA-in-noise, visual field, visual neglect, and time to complete an eye–hand coordination (EHC) task. All cases were radiologically confirmed, and 10 had left hemisphere lesions. The outcomes were compared to 20 age-matched healthy controls who were tested and retested over a similar duration using the same vision tests. The testing took 12 min.ResultsDuring the first week of admission, 19/20 (95%) AIS patients returned normal visual acuity (>6/12 VA, p = 0.11), yet 11/20 (55%) had reduced VA-in-noise (p < 0.000).Visual neglect was present in 2/20 cases. Visual field defects were present in 16/20 (80%, p < 0.001), with 7/16 (44%) being unaware of their visual field loss. All of the patients chose to use their dominant right hand despite 10 having left hemisphere lesions and 13/20 (65%, p < 0.001) returning longer times to complete the EHC tracing tasks. After 2–6 months of recovery, all stroke patients returned normal visual attention, although 3/20 (15%) continued to show reduced VA in the presence of noise masks. Seven out of 20 (35%) retained visual field defects, and 8/20 (40%, three right and five left hemisphere lesions) had visuomotor impairment. Posterior circulation territory strokes and left hemisphere lesions were more likely to result in a persistent visual field loss and visuomotor deficit.ConclusionGiven that stroke is the leading cause of neurological disability affecting over 110 million people, our findings highlight the necessity for both acute and longitudinal vision assessments subsequent to mild stroke. Exposing the persistent limitations in visual functions could aid in identifying suitability for driving and the visuomotor rehabilitation of stroke survivors.Clinical Trial Registrationhttps://www.ANZCTR.org.au/ACTRN12618001111268.aspx, identifier ACTRN12618001111268.